The Socio-Economic Struggles of the Main Character in The Wish Dragon (2021) by Chris Applehans - Ahmad Nurojab; Latifah Dwi Ariyani (Metaphor, 2026)
This research aims to analyze: 1) the "Wish Dragon" movie has certain social aspects of class differences, and 2) the main character's socio-economic struggles in the “Wish Dragon” movie. This research uses a descriptive qualitative method to analyze the movie of Wish Dragon (2021) directed by Chris Appelhans as the object of research. The data collection methods include watching, reading, identifying, classifying, and selecting. The researcher utilizes Karl Marx’s theory of Marxism to analyze the data through the steps of displaying, explaining, and interpreting. The result of this research shows that:1) the "Wish Dragon" movie has certain social aspects of class differences is reflected through the depiction of class inequality, discrimination, and limited access to opportunities for the lower class, especially through the character of Din who experiences marginalization based on his social status; 2) the main character's socio-economic struggles in the “Wish Dragon”, where the gap between the rich and the poor determines social treatment, personal relationships, and life opportunities. The film also highlights themes such as prejudice, social stratification, and the pursuit of equality through hard work and sincerity, emphasizing the importance of inner values over social class.